PERANAN MAHASISWA KKN DALAM MELAKSANAKAN KEGIATAN TAMBAHAN LOKASI PENGABDIAN DI GAMPUNG TANTUHA - Muhamad Saleh; Murni Murni; Muhammad Daud; Mardhilla Gustin; Dina Riska (LPPM Universitas Al Muslim, 2022)
Student Community Service Program (KKN) at Tantuha Village, Simpang Tiga District, Aceh Besar Regency was a form of community service activity for Abulyatama University students, which was carried out from 1 to 31 August 2022. Community service activities consisted of main activities and additional activities (group activities, partner activities and special activities). This KKN activity aimed to increase empathy and concern among the students as well as providing experiences and a learning process for students to explore village potential that can be developed by the community. The KKN implementation method consisted of survey activities and planning additional planned activities. Additional KKN student activities received support from the local government and the village community. This is shown in the KKN student activities which involved many people from various groups. The village government and its apparatus involved many KKN students in carrying out village activities, such as commemorating the 77th Independence Day of the Republic of Indonesia, posyandu and poswindu. Other forms of activities that involving young teenagers and elementary and junior high school students such as tutoring and morning exercises were carried out in the community and youth in the Tantuha village, keeping the environment clean by working together and rearranging hamlet boundaries and installing alley markers . The Abulyatama University KKN activities were expected to provide benefits to the people of Gampung Tantuha, especially to create peace and increase the interest of the children of Tantuha Village